RUPIAH EXCHANGE RATE FLUCTUATION AND CURRENT ACCOUNT - Santosa, Agus Budi; Nusantara, Agung; Nawatmi, Sri (Proceeding Fakultas Ekonomi, 2017)
The Rupiah exchange rate is an economic variable which is very sensitive toward the changes in both economy  and  non-economy.  The  stability  of  Rupiah  exchange  rate  has  influenced macro  economic variables like current account and finally influenced economic stabilities. Thus, it is interesting to make a research on it. The research would choose and analyze approach models of Rupiah exchange rate to USA dollar connected with current account.The Ordinary Least Square analysis model was used in this test in order  to  find  the  relation  between independent  variable  and  dependent  variable. The  result  of  the study showed that exchange rate variable influence significantly to current account.This conclusion was in accordance  to  elasticity approach  with  Marshall-Lerner  condition. Another  result  showed  that  gross domestic  product  influenced  current  account  significantly  and  this  was  also  in  accordance  to Global Monetary Approach Balance of Payment with purchasing power parity concept. Keywords  :  exchange  rate,  current  account,  economic  stability,  Marshall-Lerner  condition, purchasing power parity.